INFORMATION EFFICIENCY IN THE U.S. AND SHARIAH-COMPLIANT STOCKS IN MALAYSIA DURING COVID-19 - Ooi Kok Loang (Journal of Islamic Monetary Economics and Finance, 2023)
This study examines the impact of analysts’ forecast of market liquidity and information efficiency in the U.S (developed) and Malaysia (emerging – Shariah-compliant stocks) before and during COVID-19. The results show that the analysts’ forecast is significant to the market liquidity in the pre-COVID period but its influence diminishes during the COVID-19. Moreover, the impact of the analysts’ forecast is significant in the upper quantiles (0.7 and 0.9 quantiles) of the U.S market and in the lower quantiles (0.1 and 0.3 quantiles) of Malaysia's Islamic market. Similarly, the buy-sell recommendations in the U.S market and all variables forecasted are significant before COVID-19. Both markets become inefficient during COVID-19, and analysts’ forecast is no longer correlated to information efficiency. These results inform practitioners and investors to inspect the market conditions and investor's behavior under market stress such as COVID-19, which has disrupted the international financial markets.